Chavicol benzoxazine: Ultrahigh Tg biobased thermoset with tunable extended network. (August 2016) - Dumas, Ludovic; Bonnaud, Leïla; Olivier, Marjorie; Poorteman, Marc; Dubois, Philippe
Graphical abstract: Highlights: Robust synthesis of a bio based bis-benzoxazine. Allyl functionalized benzoxazine. Tunable extended network. Excellent thermomechanical properties. Abstract: A novel biobased benzoxazine monomer containing additional allyl functionality was synthesized using a solventless approach from the reaction of a natural occuring phenol: chavicol, para -phenylene diamine and formaldehyde. The chemical structure of this functionalized benzoxazine monomer was confirmed by 1 H NMR and FTIR. Its polymerization was investigated and monitored by DSC showing two well defined exotherms allowing the selective ring-opening polymerization of benzoxazine functions and the preservation of the allyl functionality. The network crosslink density could be further increased via the controlled polymerization of allyl functionalities with a post-cure in order to adjust the thermo-mechanical properties. When both networks were polymerized, the thermoset presented an excellent thermo-mechanical stability with a Tα higher than 350 °C as measured by DMTA. This exceptional behavior for a potentially biobased benzoxazine resin will allow the preparation of sustainable high performance biocomposite materials.